Cases of Pulmonary Tuberculosis Based on Nutritional Status of Ponorogo Regency in 2016-2020 - Nurfatin Tria; Nur Fatin; Rahma Samsir; Nur Faizah; Opy Linda; Nurfita Sari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The screening rate for suspected pulmonary tuberculosis cases, facilitated through health promotion activities in collaboration with the Ponorogo District Health Office, serves as a key indicator of the effectiveness of our efforts in controlling the disease. Objective: To analyze the predictive relationship between nutritional status and the incidence of pulmonary tuberculosis in Ponorogo Regency. Method: This study employed a descriptive research design to analyze a specific population at a single point in time. The sample and population consisted of nutritional status data of individuals with pulmonary tuberculosis whose sputum test results were positive in Ponorogo Regency. Results: The incidence of pulmonary tuberculosis in Ponorogo Regency increased from 276 cases in 2011 to 392 cases in 2012, followed by 378 cases in 2013. The number then decreased to 293 in 2014 and increased again to 334 in 2015. The projected decrease in cases was 299 for 2016 and 306 for 2020. The time series analysis revealed a decrease in pulmonary tuberculosis cases with positive sputum test results, which correlated with nutritional conditions. Conclusions: The application of a quadratic trend model for time series analysis demonstrated that the incidence of pulmonary tuberculosis was influenced by nutritional status, including factors such as obesity, overnutrition, normal nutrition, and malnutrition. Keywords: Pulmonary tuberculosis, nutritional status, time series analysis, health promotion, Ponorogo Regency